Ultrasensitive detection of seventeen chemicals simultaneously using paper-based sensors. (28th August 2018) - Wang, Zhongxing; Sun, Li; Liu, Liqiang; Kuang, Hua; Xu, Liguang; Xu, Chuanlai
Abstract : We developed an ultrasensitive gold nanoparticle-based multicomponent lateral-flow strip assay for the simultaneous detection of seventeen hormone drugs from three classes: nandrolone (NR) and its analogues, dexamethasone (DEX) and its analogues, and hexestrol (HES) and its analogues. Abstract : We developed an ultrasensitive gold nanoparticle-based multicomponent lateral-flow strip assay for the simultaneous detection of seventeen hormone drugs from three classes: nandrolone (NR) and its analogues, dexamethasone (DEX) and its analogues, and hexestrol (HES) and its analogues. The antibodies and coating antigens were selected for the assay and the multi-immunochromatographic strip (multi-ICS) exhibited a very low limit of detection (LOD). Quantitative results were obtained using a strip scan reader, giving LOD values of 0.06–4.85 ng mL −1 for NR and its analogues, 0.005–2.85 ng mL −1 for DEX and its analogues, and 0.03–2.14 ng mL −1 for HES and its analogues. The recovery rates from milk samples were 85.8–93.3% for NR, 78.8–87.5% for DEX, and 89.4–99.4% for HES. This multi-ICS assay therefore provides a useful tool for on-site detection and rapid initial screening of hormone drugs in biological samples.